2013
DOI: 10.1111/echo.12345
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Twisting and Untwisting Properties of the Left Ventricle during Normal Pregnancy

Abstract: During normal pregnancy, LV twist and peak untwisting rate increase in the 3rd trimester and correlate with end-systolic and end-diastolic volume, respectively. Circumferential strain of the apex and global longitudinal strain decrease from the 2nd trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
0
16
0
5
Order By: Relevance
“…With afterload held constant, increasing preload (eg, by saline infusion and in pregnancy) augments LVT and untwist 12,13 ; and with preload held constant, increasing afterload, for example, isometric handgrip, decreases LVT and untwist 14 , whereas decreasing afterload, for example, using rotates the base in a clockwise direction and the apex in a counterclockwise direction, whereas the inner endocardial layer (in red) rotates the apex and base in exactly opposite directions. Because of the larger epicardial radius (r1) and the smaller endocardial radius (r2), the epicardial rotation dominates the overall LV rotational direction.…”
Section: Changes Of Loading and Contractilitymentioning
confidence: 99%
“…With afterload held constant, increasing preload (eg, by saline infusion and in pregnancy) augments LVT and untwist 12,13 ; and with preload held constant, increasing afterload, for example, isometric handgrip, decreases LVT and untwist 14 , whereas decreasing afterload, for example, using rotates the base in a clockwise direction and the apex in a counterclockwise direction, whereas the inner endocardial layer (in red) rotates the apex and base in exactly opposite directions. Because of the larger epicardial radius (r1) and the smaller endocardial radius (r2), the epicardial rotation dominates the overall LV rotational direction.…”
Section: Changes Of Loading and Contractilitymentioning
confidence: 99%
“…Recently, using this echocardiographic technique, a small decrease in LV segmental longitudinal systolic and diastolic function, as well as changes in torsion and peak LV twist velocity, in hearts of women with otherwise normal pregnancies were reported . Thus, in the current study we employed indexes derived from both TDI and speckle tracking techniques, in addition to the more traditional methods, to study cardiac function in a unique group of patients to whom these methods have not yet been applied: those with significant SOB with no other known systemic or obstetric problem and no obvious reason on clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Global longitudinal and circumferential strain did not differ significantly in our group of patients with SOB from the control group; however, increased rotation of the base and a trend for greater torsion in the former group is in accord with reports on similar findings in patients with diastolic dysfunction. 21,23 Fonseca et al 24 found greater LV torsion by magnetic resonance imaging in patients with type 2 diabetes mellitus with diastolic dysfunction and normal LVEF than in a control group. Tzemos et al 25 reported increased twist during pregnancy in women with bicuspid and stenotic aortic valves.…”
Section: Echocardiographymentioning
confidence: 98%
“…Данные в группе контроля совпадают с данными, полученными у беременных другими исследователями [19][20][21][22][23][24].…”
Section: материал и методыunclassified
“…Сандрикова [3,12,13]. В них были определены критерии эффективности терапии у пациентов различных нозологических групп на основа-нии оценки динамики данных спекл-трекинг эхокардио-графии (Эхо-КГ) в режиме 2DT, была показана невысокая информативность ФВ, доказана целесообразность расче-та крайне актуальных для миокарда производных силы, времени и скорости с оценкой динамики сокращения миокардиальных волокон в продольном, циркулярном и радиальном направлениях [3,12,[14][15][16][17][18][19][20][21][22][23].…”
unclassified